2016
DOI: 10.1007/s10994-015-5539-3
|View full text |Cite
|
Sign up to set email alerts
|

Subjective interestingness of subgraph patterns

Abstract: The utility of a dense subgraph in gaining a better understanding of a graph has been formalised in numerous ways, each striking a different balance between approximating actual interestingness and computational efficiency. A difficulty in making this trade-off is that, while computational cost of an algorithm is relatively well-defined, a pattern's interestingness is fundamentally subjective. This means that this latter aspect is often treated only informally or neglected, and instead some form of density is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…By De Bie [4], it was argued to choose P as the Iprojection of the previous background distribution onto the set of distributions consistent with the presented pattern. Then Van Leeuwen et al [19] showed that the resulting P is again a product of Bernoulli distribution:…”
Section: The Background Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…By De Bie [4], it was argued to choose P as the Iprojection of the previous background distribution onto the set of distributions consistent with the presented pattern. Then Van Leeuwen et al [19] showed that the resulting P is again a product of Bernoulli distribution:…”
Section: The Background Distributionmentioning
confidence: 99%
“…Given a pattern (W 1 , W 2 , I, k W ), and a background distribution defined by P , the probability of the presence of the pattern is the probability of getting k W or more (for I = 0), or fewer than k W (for I = 1) successes in n W trials with possibly different success probabilities p u,v . While it is impractical to compute these probabilities exactly, using the same approach as Van Leeuwen et al [19] they can be tightly upper bounded using the general Chernoff/Hoeffding bound [9], as follows:…”
Section: The Subjective Interestingness Measurementioning
confidence: 99%
“…where w(e) −log(Pr(µ(e) ≥ e )) denotes the information content of the edge e, with Pr(·) denoting the probability under the background distribution P. Note that w(e) ≥ 0 for all e ∈ V × V . e DL can be computed similarly as in the work of Leeuwen et al [17]. To communicate a cycle pa ern C to the user, we need to communicate |C | nodes.…”
Section: Subjective Interestingness Of Cycle Patternsmentioning
confidence: 99%
“…As shown in [6], given prior beliefs on the degrees of the nodes, the maximum entropy distribution factorizes as:…”
Section: Prior Beliefs On Overall Density and On Individual Node Degmentioning
confidence: 99%
“…In general, an edge will have a high probability if the corresponding expected block diagonal sum is high, see Eqs. (3) and (6). Note that the citation network should (in theory) be a directed acyclic graph, since no paper can cite a paper with a higher publication year.…”
Section: The Effect Of Different Prior Beliefs and A Subjective Evalmentioning
confidence: 99%